Design, synthesis, and application of new Ti precursors compatible with Ba and Sr precursors for BST thin film by MOCVD - Woo, K (EDP SCIENCES S A, 2002)
Design, synthesis, and application of the new Ti precursors [Ti(MPD)(MDOP)(2) and the binuclear precursor D (designated as D due to patent pending) derived from thereof] for MOCVD of TiO2 thin film are reported. The new Ti precursors are stable in the air and moisture and thermally stable at vaporizing temperature. The deposition rate of TiO2 films with the new Ti precursor D was much higher than that with Ti(MPD)(tmhd)(2) or with Ti(Opr(i))(2)(tmhd)(2) at 375similar to475degreesC. Therefore, the new Ti precursors are expected to yield BST thin films with constant composition in Ba, Sr, and Ti utilizing the prevalent Ba and Sr precursors and current MOCVD technology. It is believed that the high deposition rate of TiO2 thin film is caused by the weaker bond strength of Ti-MDOP than Ti-tmhd.
Keywords: CHEMICAL-VAPOR-DEPOSITION; (BA